Particle residence time distributions in a vortex-based solar particle receiver-reactor: An experimental, numerical and theoretical study. (16th March 2020) - Davis, Dominic; Troiano, Maurizio; Chinnici, Alfonso; Saw, Woei L.; Lau, Timothy; Solimene, Roberto; Salatino, Piero; Nathan, Graham J.
Highlights: Particle residence time distributions measured in a novel solar particle receiver. Systematic variation of particle size, gas volumetric flow rate and inlet velocity. Two regimes of particle behaviour, characterised by the Stokes and Froude numbers. Compartment model of plug flow reactor followed by two interconnected CSTRs. Abstract: We report a joint experimental, numerical and theoretical study of particle residence times in a novel vortex-based vessel for thermal processing of suspended particles. The tracer pulse-response method, in which the particle phase itself is employed as the tracer, is used to measure the particle residence time distribution (RTD) within a laboratory-scale model of a class of Solar Expanding Vortex Receiver-Reactor (SEVR). The operating parameters of particle size, gas volumetric flow rate and inlet velocity were systematically varied to assess their influence on the particle RTD and to determine the mechanisms controlling the behaviour of the two-phase flow in the SEVR. The particle RTD behaviour is also described by a compartment model consisting of a small plug flow reactor followed by a series of two interconnected continuously-stirred tank reactors (CSTRs).